Universiti Putra Malaysia Goes The (Long) Distance - New Straits Times, (2008)
Universiti Putra Malaysia (UPM) bring higher education to your doorstep through its distance learning (PJJ) programmes, under the External Education Centre (Pusat Pendidikan Luar), which was formed in 1995.